Two-Step Thermochemical CO2 Splitting Using Partially-Substituted Perovskite Oxides of La0.7Sr0.3Mn0.9X0.1O3 for Solar Fuel Production - Sawaguri, Hiroki; Gokon, Nobuyuki; Hayashi, Kosuke; Iwamura, Yoshikazu; Yasuhara, Daichi (Frontiers in Energy Research, 2022)
We investigated, herein, the redox activity of partial substitution of the B-site in a series of lanthanum/strontium-manganese-based (LSM) perovskite oxide, La0.7Sr0.3Mn0.9X0.1O3 for solar two-step thermochemical fuel production using concentrated solar radiation as an energy source. We systematically investigated the effects of partial substitution in LaSrMnO3 in terms of their kinetics behavior, oxygen/CO productivity, thermal reduction/oxidation temperatures. Furthermore, repeatability was evaluated and compared among the samples prepared using the same procedure and studied using the same test method. We observed and evaluated the long-term thermal stability of the redox activity and valence variation of the constituting ionic species of the perovskite in the two-step thermochemical CO2 splitting. From the perspectives of superior activity and long-term repeatability, Ni-, Co-, and Mg-substituted LSM perovskites are promising for thermochemical two-step CO2/H2O splitting to produce synthetic gas.